2007
DOI: 10.1107/s1600536807038342
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bonding patterns in pyrimethaminium 3,5-dinitrobenzoate

Abstract: Key indicators: single-crystal X-ray study; T = 293 K; mean (C-C) = 0.004 Å; R factor = 0.049; wR factor = 0.144; data-to-parameter ratio = 13.5.In the crystal structure of the title compound [systematic name: 2,4-diamino-5-(4-chlorophenyl)-6-ethylpyrimidin-1-ium 3,5-dinitrobenzoate], C 12 H 14 ClN 4 + ÁC 7 H 3 N 2 O 6 À , the pyrimethamine molecule is protonated at one of the pyrimidine N atoms. The carboxylate group of the 3,5-dinitrobenzoate anion forms double hydrogen bonds of type N-HÁ Á ÁO, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…. This type of array has also been identified in trimethoprim hydrogen glutarate (Robert et al, 2001), trimethoprim formate (Umadevi et al, 2002), trimethoprim-m-chlorobenzoate (Raj et al, 2003), pyrimethaminium 3,5-dinitrobenzoate (Subashini et al, 2007) and 2-amino-4,6-dimethoxypyrimidinum-salicylate (Thanigaimani et al, 2007). An infinite number of several such quadruple arrays are interconnected and stabilized by π-π stacking interactions between the pyrimidine ring of one array with a neighbouring array, with an observed interplanar distance of 3.356 Å, a centroid (Cg1)-to-centroid (Cg1) distance of 3.4689 (12) Å (where Cg1 equals the centroid of the ring N1/C1/N2/C2/C3/C4, Fig 3) and slip angle (the angle between the centroid vector and the normal to the plane) of 14.68°, which are typical aromatic stacking values (Hunter, 1994 (Table 2).…”
Section: S1 Structural Commentarymentioning
confidence: 92%
See 1 more Smart Citation
“…. This type of array has also been identified in trimethoprim hydrogen glutarate (Robert et al, 2001), trimethoprim formate (Umadevi et al, 2002), trimethoprim-m-chlorobenzoate (Raj et al, 2003), pyrimethaminium 3,5-dinitrobenzoate (Subashini et al, 2007) and 2-amino-4,6-dimethoxypyrimidinum-salicylate (Thanigaimani et al, 2007). An infinite number of several such quadruple arrays are interconnected and stabilized by π-π stacking interactions between the pyrimidine ring of one array with a neighbouring array, with an observed interplanar distance of 3.356 Å, a centroid (Cg1)-to-centroid (Cg1) distance of 3.4689 (12) Å (where Cg1 equals the centroid of the ring N1/C1/N2/C2/C3/C4, Fig 3) and slip angle (the angle between the centroid vector and the normal to the plane) of 14.68°, which are typical aromatic stacking values (Hunter, 1994 (Table 2).…”
Section: S1 Structural Commentarymentioning
confidence: 92%
“…For crystal structures of related salts, see: Ebenezer et al (2012); Jennifer & Muthiah (2014). DDAA arrays have been observed in trimethoprim hydrogen glutarate (Robert et al, 2001), trimethoprim formate (Umadevi et al, 2002), trimethoprim-m-chlorobenzoate (Raj et al, 2003), pyrimethaminium 3,5-dinitrobenzoate (Subashini et al, 2007) and 2-amino-4,6-dimethoxypyrimidinum-salicylate (Thanigaimani et al, 2007). Table 1 Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%
“…Balasubramani et al [51] reported the same hydrogen bonding in the salt formed from pyrimethamine and picolinic acid. Devi et al [52] and Subashini et al [53] reported similaro bservations when investigating the formation of salts formed by pyrimethamine with 3-chlorobenzoate and 3,5-dinitrobenzoate,r espectively,i nw hich NÀH···O hydrogen bonds link the two components.…”
Section: Pyrimidine-containing Apismentioning
confidence: 99%